B-Flow imaging of the placenta: A feasibility study. (August 2018) - Dighe, Manjiri K; Moshiri, Mariam; Jolley, Jennifer; Thiel, Jeff; Hippe, Dan
B-Flow imaging directly displays the flowing intravascular echoes during real-time gray-scale ultrasound without using Doppler techniques. The objective of our study was to evaluate the feasibility of B-Flow imaging in the placenta and to evaluate the artifacts seen on B-Flow imaging. After IRB approval, 36 women (17 normal and 19 high risk women) were enrolled in our study. B-Flow images were acquired on GE LOGIC E9 machine. Retrospective analysis of the B-Flow and cine capture images was performed for artifacts and for vessels visualized. Pregnant women enrolled in the study ranged from 19 to 43 years of age with an average age of 31.7 years. Gestational age varied from 17 weeks and five days to 36 weeks and three days with an average of 26 weeks and three days. From a total of 161 B-Flow images reviewed by one researcher, 15 images were acceptable with no evidence of artifact. The remainder of the images had some artifact in them. For the 36 women with color Doppler and B-Flow images reviewed by the two independent blinded reviewers, a total of 144 reads were obtained. More small horizontal (p = 0.046) and small vertical running vessels (p < 0.001) were identified with B-Flow than color Doppler images. B-Flow is capable of showing perfusion in a human placenta; however, recognizing artifacts and modifying the image acquisition to reduce artifacts is necessary with this new technique to acquire the best images for interpretation.